Program Deteksi Dini dan Edukasi Kesehatan Mental Remaja melalui Peer Educator di SMP Sains Terpadu Darussa'adah Pace Nganjuk - Iswanto, Juni; Tohawi, Agus; Mas'ud (Ngaliman: Jurnal Pengabdian Kepada Masyarakat, 2025)
This program implements an integrated Early Detection and Mental Health Education initiative for adolescents at SMP Sains Terpadu Darussa'adah Pace, Nganjuk, utilizing a Peer Educator model. Selected students undergo training to become peer educators, equipping them with foundational knowledge of adolescent mental health, skills to recognize early signs of psychological distress, and techniques for providing basic peer support. These trained peers actively disseminate mental health information, foster awareness, and reduce associated stigma among the student body. Crucially, they serve as accessible first points of contact, identifying peers potentially struggling and facilitating timely referrals to professional school resources like guidance counselors (BK Teachers) or psychologists. The program successfully creates a more supportive school environment, empowers students through peer-led education, and establishes a proactive system for early intervention. This approach enhances overall mental well-being and promotes help-seeking behavior within the junior high school setting.